Optimizing Data Transmission in Wireless Sensor Networks Using Machine Learning - Olusegun Adebayo Johnson; Chukwuemeka Ayodele Obi (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2024)
Data transmission efficiency is crucial in wireless sensor networks (WSNs), where limited battery life and signal reliability are significant concerns. This research explores various machine learning algorithms aimed at optimizing data transmission in WSNs, focusing on reducing energy consumption and enhancing network stability. Simulation results indicate marked improvements in efficiency, making WSNs more viable for long-term deployment across diverse environments.